Systematic Review of Potential Occupational Respiratory Hazards Exposure Among Sewage Workers - Muzaini, Kamarulzaman; Yasin, Siti Munira; Ismail, Zaliha; Ishak, Ahmad Razali (Frontiers in Public Health, 2021)
Background: Sewage workers have a higher risk of exposure to various potential occupational respiratory hazards found in the sewage plants. Although previous studies discussed occupational respiratory hazards concentration impacting sewage workers’ respiratory health, the results were scarce and mixed. Hence, there is a need to identify the potential respiratory hazards in sewage plants as to clarify the short-term and long-term respiratory health effects. Therefore, this systematic review (SR) aims to critically review previous studies investigating potential respiratory hazards found at the sewage plants and their effects on the sewage workers’ respiratory health. Methods: A SR was conducted using PubMed, EBSCO Medline, Web of Science, Scopus, and Google Scholar on peer-reviewed studies published between January 1994 and October 2020, evaluating the impact of potential exposure to respiratory hazards and its effects on the respiratory health among sewage workers. "Sewage treatment plant", "respiratory hazards", and "respiratory health effects" were the three main search terms chosen in this SR. The inclusion criteria were 1) studies on potential occupational respiratory hazards exposure among sewage workers, 2) manuscripts written in English, and 3) published in the peer-reviewed literature. The human observational studies quality were assessed using the Effective Public Health Practice Project Quality Assessment Tool. Results: We had identified 5,660 articles through an initial database search. Only 26 items met the inclusion criteria and were included in this review; 15 human observational studies and 11 environmental assessment studies were conducted at the sewage industries. Most of the human observational studies were rated as moderate-quality, two studies rated as weak-quality review, and one study with strong-quality was identified. Hydrogen sulfide, bioaerosols, PM 2.5, and VOC were found to be potential respiratory hazards. Most of the risks had contributed to adverse outcomes on the sewage workers’ respiratory health with some inconsistent findings on the relationship between respiratory hazards exposure and respiratory health effects. Conclusion: Our review found that although this area is of great importance, quality studies are still lacking. There is a need for additional studies to clarify the effects of respiratory hazards exposure on the sewage workers, and respiratory health, especially PM 2.5 and VOC.